The Influence of Profitability, Sales Growth, and Capital Intensity on Tax Avoidance - Delia Ramadina; Juniati Gunawan (SAFE-Network, 2023)
This study aims to examine the influence of profitability, sales growth, and capital intensity on tax avoidance in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This study uses secondary data from the company's financial reports and annual reports. The method used in this research is regression analysis with SPSS version 25. The results of this study indicate that profitability and sales growth have a positive influence on tax avoidance. Capital intensity has no influence on tax avoidance and leverage as a control variable affects the independent variable on tax avoidance.